Evaluation of Gastric Emptying in Cystic Fibrosis Using Bedside Ultrasonography. (28th March 2019) - Nazareth, Dilip; Mohan, Kamlesh; Fewins, Hilary; Walshaw, Martin
Abstract : Objectives: Although gastric emptying rate (GER) influences incretin response and nutrient absorption, both defective in people with cystic fibrosis (CF), there are few studies in this group, and the circadian rhythm is unknown. We employed an ultrasonographic technique to assess GER in people with CF following liquid and mixed meals and also evaluated the circadian rhythm, compared to normal controls. Methods: Thirteen pancreatic‐insufficient adults with CF and 10 healthy controls underwent a fasting oral glucose tolerance test (OGTT; liquid meal) and on a second visit underwent a fasting mixed meal test (MMT) thrice on the same day. GER was measured during the OGTT and each MMT using a 3.5‐MHz abdominal transducer probe at baseline and 30, 60, 90, and 120 minutes. Results: Controls had normal GER for both OGTT and MMT. Compared to controls, people with CF had delayed GER60 for OGTT (mean 46%), which increased with time ( P  = .001), and also delayed GER90 for MMT in the morning (mean 56%), afternoon (58%), and evening (59%). The GER in the control group was better at all time points throughout the day compared to patients with CF. Conclusions: This is the first study to use ultrasonography, an inexpensive bedside technique, to assess GER in adults with CF. For the first time, we have shown that adults with CF have delayed GER for both liquid and mixed meals, and this delay continues throughout the day.